SELF-CONTROL AND READINESS TO CHANGE AMONGST RECOVERING ADDICTS - Vijayakone, Brindha; Lim Abdullah, Haslee Sharil; W.N.H, Othman; Mohd Yusof, Siti Nubailah (International Journal of Psychosocial Rehabilitation, 2021)
Purpose: This study was done to identify and measure Self-Control and Readiness to Change amongst recovering addicts plus it also aims to compare recovering addicts’ Self-Control and Readiness to Change mean score based on age, race, marital status, educational level and duration involved in drugs. The relationship between Self-Control and Readiness to Change amongst recovering addicts also were examined in this study. Methodology: Study involved 190 respondents, randomly selected from a Cure and Care Rehabilitation Centre (CCRC) located in the state of Johor. Instruments used to measure the levels were the Self-Control Scale and the University of Rhode Island Change Assessment Scale (URICA). The quantitative descriptive design was applied and the questionnaire method was used to obtain data. Statistical Package for Social Science (SPSS) version 22.0 using descriptive, t-tests and correlation statistical analysis were used to analyze the data. Findings: Research findings showed that levels of Self-Control amongst recovering addicts were at an average level and the Readiness to Change amongst recovering addicts were at the Contemplation stage. There were no significant differences in recovering addicts’ SelfControl and Readiness to Change mean score based on the demographic variables examined. The findings of this study also showed an inverse correlation between Self-Control and Readiness to Change (r = - 0.15, n = 190, p = 0.04). However, the results cannot be generalized because the sample does not represent the population of all recovering addicts in Malaysia. Implications: The information gathered from this study is useful for understanding the level of Self-Control and Readiness to Change amongst recovering addicts, hence it can be emphasized in future drug prevention and rehabilitation programs in Malaysia. Originality of this study: Drug addiction problem in Malaysia is vastly increasing and there are many measures being taken to curb this problem. Hence, this study emphasizes on the importance of Self-Control and Readiness to Change for recovering addicts to gain a positive and healthy lifestyle. However, in this study its showed that, even if there is help and support from others, a change can only occur if the individual is prepared mentally and physically.